NATO enlargement to the East and the war in Ukraine from the American perspective - Jureńczyk, Łukasz (Przegląd Wschodnioeuropejski, 2024)
The aim of the article is to analyze the legitimacy of justifying the outbreak of war in Ukraine by expanding NATO to the East after the Cold War. The study was conducted from the American perspective. The main research problem is the question of whether, from the point of view of American scholars and experts, post-Cold War NATO expansion to the East was a strategic mistake and was responsible for the current war in Ukraine. There is no consensus among them whether NATO enlargement after the Cold War was an error and led to Russian aggression in Ukraine. Most of them, however, dispute such a statement, rejecting Moscow’s accusations that the United States and the West are accountable for the current situation in Ukraine.